INTEGRATING TECHNOLOGY AND ARTIFICIAL INTELLIGENCE IN SECONDARY EDUCATION: IMPACTS ON LEARNING MOTIVATION AND ACADEMIC ACHIEVEMENT - Gadir, Hulud (E-Journal VFU, 2025)
This paper examines the transformative role of integrating technology and artificial intelligence (AI) in secondary education and its multifaceted impact on learning motivation and academic achievement. Relying entirely on previous studies and extensive literature, this work synthesizes evidence from diverse sources to demonstrate how digital tools, AI-driven personalized learning systems, and modern technological infrastructures reshape traditional classroom dynamics. The review reveals that effective integration of these innovations can enhance student engagement, promote individualized learning, and foster intrinsic motivation, while also highlighting challenges such as the digital divide and ethical concerns. Drawing on empirical studies and theoretical frameworks from researchers such as Zahran Sana (2013), Fatima al-Zahra (2017), and Hattie (2009), the paper concludes with comprehensive insights and recommendations for policymakers and educators. The conclusions and summary are entirely based on the literary review, emphasizing the need for balanced, human-centered educational strategies that leverage technology to its fullest potential.
Keywords: Technology integration; Artificial intelligence; Learning motivation; Secondary education